GLOBAL EXPERIENCE OF FINANCIAL REGULATIONS OF THE AGRO-INDUSTRIAL COMPLEX AND SERBIAN ENTREPRENEURIAL AGRICULTURE IN MODERN BUSINESS - Ilić, Biljana; Anđelić, Slavica; Pavićević, Nina (Economics of Agriculture, 2026)
The paper analyzes international practices in the financialregulation of the agro-industrial complex, with a specialfocus on the Republic of Serbia and the improvementof sustainable sector development under economicchallenges. Particular attention is given to innovativefinancial instruments, including agrifintech, crowdfunding,and index insurance, as well as to the experiences ofthe United States, the European Union and China. Theresearch applies a comparative analysis of financialregulatory models, institutional frameworks, and financingmechanisms. The findings highlight the importance ofdigitization and innovative financial models for improvingaccess to capital and strengthening the competitiveness ofsmall and medium-sized agricultural farms. The study alsoidentifies key barriers, including inadequate infrastructure,low digital literacy, and regulatory limitations. The papercontributes to the literature by integrating traditionaland modern financial instruments within the context oftransition economies.